Automatic image annotation based on shape / Norazirah Ramli - Ramli, Norazirah (2009)
The project is titled Automatic Image Annotation based on Shape. This project annotated people and rock in the beach scenery images. The project also used global shape descriptors approach in the annotating. Nowadays, there are many approaches in automatic annotation system. One of the ways is through region-based technique that involved is global shape descriptors. Even though, these projects choose to use compactness and eccentricity technique which are suitable for non-occluded object. The techniques were applied after image pre-processing stage. Several steps such grayscale, segmentation and dilation have been used to pre-processing the images. Then, the objects in the images were determined. Finally, the image is annotated through the caption the object of the image.